Estudo fitoquímico e atividade biológica de constituintes das folhas e galhos de Maytenus robusta (Celastraceae) - Grasiely Faria de Sousa (2016)
The phytochemical study of the leaves and branches from Maytenus robusta resulted in the isolation of thirteen pentacyclic triterpenes: 3-oxofriedelane (MR01), 3ß-hydroxyfriedelane (MR02), 3ß11ß-dihydroxyfriedelane (MR03), taraxerol (MR04), 3,16-dioxofriedelane (MR09), 3-oxo-29-hydroxyfriedelane (MR10), 3,16-dioxo-12-hydroxyfriedelane (MR11), 3,16-dioxo-29-hydroxyfriedelane (MR12), 3,16-dioxo-friedelan-1-ene (MR13), 3-oxo-16,29-di-hydroxyfriedelane (MR14), 1[alfa],29-di-hydroxy-3-oxofriedelane (MR15), 3-oxo-12[alfa],29-dihydroxyfriedelane (MR16) and 3-oxo-16,28,29-trihydroxyfriedelane (MR17). The steroid sitosterol and the flavonoids kaempferol (MR06), kaempferol-3-O-ß-D-glucopyranosyl-(13)-ß-L- rhamnopyranosyl-(12)-ß-D-glucopyranoside (MR07) and quercetin-3-O-ß-D-glucopyranosyl-(13)-[alfa]-L-rhamnopyranosyl-(12)-ß-D-glucopyranoside (MR08) were also isolated. The triterpenes MR12, MR13, MR14, MR15 and MR17 and the flavonoids MR07 and MR08 are new compounds. The triterpenes MR09, MR10, MR12, MR14 and MR16 were submitted to reduction reaction using sodium borohydride as reducing agent and it was possible to obtain new compounds withbiological potential. The study of the biological activity of crude extracts and isolated compounds consisted of the evaluation of in vitro cytotoxic property, antiinflammatory, antimicrobial (antibacterial, antifungal and leishmanicidal) and acetylcholinesterase inhibitory activities. The triterpenes MR01, MR02, MR09, MR10, MR12 and MR14 presented in vitro cytotoxicity activity against 4T1 cells. In the anti-inflammatory activity study, MR09, MR10, MR12 and MR14 were able to reduce the carrageenan-induced paw edema in rats. The methanolic extracts fromleaves and branches also exhibit anti-inflammatory activity. The phytochemical and biological studies of the M. robusta contributed to know more about Celastraceae family and show the biological potential of this species.